Nature index - Abdul Shukor, Shureen Faris; Khamis, Shamsul; Abu Bakar, Shamsul; Baharuddin, Nasir; Salehuddin, Adam (Universiti Putra Malaysia Press, 2015)
Among the benefits of having birds as part of the environment include increased wildlife populations, soil conservation, natural beauty enhancement, bird-watching activity promotion, natural insect control, contributing in the food production and most importantly, property value increase. The basic considerations when designing the outdoor environment to attract birds includes sufficient food, water, shelter, diversity in the plants, the arrangement of the spaces and, provide protection from predators.